Setting multinational risk tolerance criteria. Issue 2 (30th August 2014) - Baybutt, Paul
Abstract : Companies that operate in multiple locations around the world face the challenge of developing consistent risk tolerance criteria across their operations in various locations. However, the views of local stakeholders on the tolerability of the risks can vary significantly from one location to another. Indeed, the actual risks that people are exposed to and currently tolerate can vary significantly depending on local factors. The challenges in developing consistent criteria for such multiple locations are described and addressed in this article. Regulators in several countries have developed numerical risk tolerance criteria and require that facilities meet them. The procedures used in the development of such criteria are described and form the basis for a method that is suggested for setting consistent criteria across national boundaries. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 153–158, 2016